2020
DOI: 10.3390/foods9081020
|View full text |Cite
|
Sign up to set email alerts
|

Dairy by-Products Concentrated by Ultrafiltration Used as Ingredients in the Production of Reduced Fat Washed Curd Cheese

Abstract: In the following study, three different dairy by-products, previously concentrated by ultrafiltration (UF), were used as ingredients in the production of reduced-fat (RF) washed curd cheeses in order to improve their characteristics. Conventional full-fat (FF) cheeses (45% fat, dry basis (db)) and RF cheeses (20–30% fat, db) were compared to RF cheeses produced with the incorporation of 5% concentrated whey (RF + CW), buttermilk (RF + CB) or sheep second cheese whey (RF + CS). Protein-to-fat ratios were lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Borges et al . (2020) reported that yellowness and greenness during the storage of reduced‐fat cheese with concentrated whey were mostly impacted by its fat content. In our study, modified cheeses were 28% lower in fat (Table 1) compared to control.…”
Section: Resultsmentioning
confidence: 99%
“…Borges et al . (2020) reported that yellowness and greenness during the storage of reduced‐fat cheese with concentrated whey were mostly impacted by its fat content. In our study, modified cheeses were 28% lower in fat (Table 1) compared to control.…”
Section: Resultsmentioning
confidence: 99%
“…The use of SMP for the standardization of whole milk for cheese manufacturing offers several advantages including high yield [ 7 ]. As well as this, some research has been done with the aim of determining the influence of using ultrafiltered milk retentate, milk protein concentrate and phosphocasein on the quality and characteristics of produced cheese [ 1 , 8 , 9 , 10 ]. In contrast, milk standardization is not often carried out in traditional small-scale dairy plant cheese production, which could lead to the reduced recovery of milk fat to cheese and so lesser financial profit.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced fat cheeses with 5% incorporation of buttermilk presented the best results, both concerning texture parameters and sensory evaluation. However, the authors indicate that adequate mixtures of such by-products should be tested for similar purposes [ 75 ].…”
Section: Liquid Whey and Second Cheese Whey Concentratesmentioning
confidence: 99%